2022
DOI: 10.1026/0049-8637/a000257
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Motivational Regulation Strategies for Specific Motivational Problems

Abstract: Abstract. Learners utilize a variety of strategies to regulate their motivation. Theoretical models of motivational regulation imply a connection between the decision for a concrete strategy and the specific situational requirements. Accordingly, one would expect that the suitability of a strategy depends on how well it fits the motivational problem in question. Since reliable findings on this point are missing, we conducted a survey of N = 33 proven experts in the field of self-regulated learning to enlighten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Furthermore, students could be encouraged to share these successful self-regulatory experiences with other students, thus serving as authentic role models (i.e., providing vicarious mastery experiences for others). Additionally, students can be assisted in elaborating on the suitability of concrete strategies for specific motivational problems in terms of conditional strategy knowledge (Eckerlein et al, 2022; Steuer et al, 2019) and in assessing the accuracy and quality of their application (Engelschalk et al, 2017; Leutner et al, 2001). Finally, they can be supported in detecting different kinds of motivational problems through conscious metamotivational monitoring (Miele & Scholer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, students could be encouraged to share these successful self-regulatory experiences with other students, thus serving as authentic role models (i.e., providing vicarious mastery experiences for others). Additionally, students can be assisted in elaborating on the suitability of concrete strategies for specific motivational problems in terms of conditional strategy knowledge (Eckerlein et al, 2022; Steuer et al, 2019) and in assessing the accuracy and quality of their application (Engelschalk et al, 2017; Leutner et al, 2001). Finally, they can be supported in detecting different kinds of motivational problems through conscious metamotivational monitoring (Miele & Scholer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in line with our observation that MR and ER show strongest conceptual correspondence in strategies involving cognitive reframing of subjective expectancy-/control-and value-related perceptions, we found that levels of ability-focused self-talk, control-enhancing reappraisal, enhancing personal significance, value-enhancing reappraisal, mastery self-talk, and self-consequating were smaller between motivational vs. emotional problems than between expectancy vs. value problems. However, not all of these strategies differed for expectancy-vs. value-related problems as one may expect based on past work on the situational fit of MR strategies (Eckerlein et al, 2022). For instance, mean levels of value-enhancing reappraisal were slightly higher for expectancy problems as compared with value problems, which seems counterintuitive.…”
Section: Summary Interpretation and Implications Of Findingsmentioning
confidence: 76%
“…Strategies should be matched accordingly: For instance, a student doubting their chances for completing a task should engage in strategies like ability-focused self-talk to increase perceptions of personal competence and success expectancies. Initial evidence drawing on student (Engelschalk et al, 2016) and expert ratings (Eckerlein et al, 2022) supports the idea that-variability notwithstanding-MR strategies can be categorized as primarily catering to either expectancy or value problems, or to both ('universal strategies'). Emergent scholarship on educational ER also indicates that effective regulation is not only person-, but also emotion-and contextspecific in that specific emotional experiences require different strategies (Rottweiler & Nett, 2021;Rottweiler et al, 2023).…”
Section: Problem Specificity In Mr and Er Strategy Usementioning
confidence: 96%
See 2 more Smart Citations